Block trade contracting - Baldauf, Markus; Frei, Christoph; Mollner, Joshua (Journal of Financial Economics, 2024)
We study the optimal execution problem in a principal–agent setting. A client contracts to purchase from a dealer. The dealer hedges, buying from the market, creating temporary and permanent price impact. The client chooses a contract, which specifies payment as a function of market prices; hidden action precludes conditioning on the dealer’s hedging trades. We show the first-best benchmark is theoretically achievable with an unrestricted contract set. We then consider weighted-average-price contracts, which are commonly used. In the continuous-time limit, the optimal weighting entails a constant density at interior times and discrete masses at the extremes.